Growth, phenological response, and yield of cucumber as influenced by variety, plant spacing and NPK fertilizer rate under tropical conditions - Falaiye, Olamide Oluwatosin; Adeyemi, Nurudeen Olatunbosun; Oni, Olanrewaju Emmanuel; Somoye, Rukayat Adeola; Kasali, Asimiu Olusegun; Falaiye, Oluwatosin Mary; Adekunle, Elizabeth Adeola (International Journal of Horticultural Science, 2026)
Cucumber (Cucumis sativus L.) is the fourth most cultivated vegetable globally and an increasingly important cash crop in Nigeria. Yield stagnation from suboptimal variety selection, inappropriate plant spacing and inadequate fertiliser management constrains smallholder productivity in the humid tropics. This study determined the optimal combination of variety, plant spacing and NPK 15-15-15 fertiliser rate for maximising growth and fruit yield under tropical field conditions in the forest-savanna transition zone of SW Nigeria. Two field trials were conducted at FUNAAB (7°15′N, 3°25′E) in 2019 and 2020 using a split-split plot RCBD with three replications, evaluating two varieties (CU 999 and Monalisa), three plant spacings (75×25, 75×50, 75×75 cm) and four NPK rates (0, 100, 200, 300 kg ha⁻¹). Variety CU 999 produced significantly higher fruit yield (up to 9.18 t ha⁻¹) than Monalisa across all trials. Plants at 75×25 cm spacing consistently achieved the highest yield per hectare. NPK at 300 kg ha⁻¹ reduced days to 50% flowering by 3.8–6.4 days and increased yield across trials. The three-way interaction (Variety × Spacing × Fertiliser) was significant for fruit yield, with CU 999 × 75×25 cm × 300 kg ha⁻¹ recording peak performance. CU 999 sown at 75×25 cm and fertilised with 300 kg ha⁻¹ NPK 15-15-15 is recommended for maximum cucumber yield in the forest-savanna transition zone of Nigeria.